2015
DOI: 10.3389/fncel.2015.00158
|View full text |Cite
|
Sign up to set email alerts
|

The methyl-CpG-binding domain (MBD) is crucial for MeCP2’s dysfunction-induced defects in adult newborn neurons

Abstract: Mutations in the human X-linked gene MECP2 are responsible for most Rett syndrome (RTT) cases, predominantly within its methyl-CpG-binding domain (MBD). To examine the role of MBD in the pathogenesis of RTT, we generated two MeCP2 mutant constructs, one with a deletion of MBD (MeCP2-ΔMBD), another mimicking a mutation of threonine 158 within the MBD (MeCP2-T158M) found in RTT patients. MeCP2 knockdown resulted in a decrease in total dendrite length, branching, synapse number, as well as altered spontaneous Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The methyl-CpG-binding domain (MBD) of MeCP2 is crucial for its function as a transcriptional repressor. Zhao et al provide further evidence from cultured hippocampal neurons and in vivo newborn neurons that mutations of MBD affect the roles of MeCP2 in neuronal development (Zhao et al, 2015 ).…”
Section: Molecular Synaptic and Cellular Deficits In Asdsmentioning
confidence: 99%
“…The methyl-CpG-binding domain (MBD) of MeCP2 is crucial for its function as a transcriptional repressor. Zhao et al provide further evidence from cultured hippocampal neurons and in vivo newborn neurons that mutations of MBD affect the roles of MeCP2 in neuronal development (Zhao et al, 2015 ).…”
Section: Molecular Synaptic and Cellular Deficits In Asdsmentioning
confidence: 99%
“…Adult (5-6-week-old) female C57Bl/6 mice were purchased from the SingHealth Experimental Medicine Centre, Singapore, and housed in the Specific Pathogen Free animal facility at Duke-NUS Graduate Medical School, Singapore. The surgical and postsurgical procedures were performed as described previously (13,37).…”
Section: Methodsmentioning
confidence: 99%
“…To prevent biased quantification, all counting and analysis were done blindly. The dendritic structure of newborn neurons was analyzed according to previously published methods (13,37). A total of 25-30 neurons from 4 -6 animals per experimental group were analyzed.…”
Section: Nrp2-dependent Cell Positioning Of Newborn Neuronsmentioning
confidence: 99%
“…They have also reported that newly matured neurons in MeCP2 KO mice have reduced dendritic spine density. Further, their results showed that mutations of MBD affected the roles of MeCP2 in neuronal development in cultured hippocampal neurons and in vivo newborn neurons [73]. Moreover, it has been shown that loss of MBD1 leads to autism like behavioral and learning deficits in mice, anxiety, depression, abnormal brain serotonin activity and HPA axis regulation [72,74].…”
Section: Asdsmentioning
confidence: 96%